(Malaria in Saudi Arabia in the last six years (2011-2016 - Khalifa, AM; AlShammari, A; AlShubrmi, D; Alreshidi, M; Albaqawi, R; ALShammary, R (Journal of medical and pharmaceutical sciences, 2017)
Introduction: Kingdom of Saudi Arabia ( KSA)  suffered an outbreak of malaria in 1998, Effective strategies to shrink the malaria map were carried out. Aim: to through light on recent reports of malaria disease in KSA from 2011 till 2016.Methodology: The present study searched the previous publications in the last five years from 2011 till 2016 about malaria in the KSA. Then the collected data were arranged accordingly into:1 The geographical distribution and prevalence of malaria in Saudi Arabia. 2. The species of Plasmodium present. 3. Clinical presentation in different areas in the kingdom 4. Methods of diagnosis used. 5. Methods of treatment in kingdom. 6. Methods used to control malaria in KSA. Study design: Review article , Peroid of time: Four months. Data Source: Data for this review were identified by literature searches of PubMed and general searches using the Google and WHO search engines. Also, National Library of Medicine via the PubMed and MEDLINE were used for research articles, reviews, books, and other reports. We searched by using key word searches such as “malaria” and “Saudi Arabia”. Results:  The number of malaria cases in Saudi Arabia decreased between 2011 and 2016.. Incidence continued to be reported at low levels (between 0.01 and 0.1 per 1,000 of the population) with: P. falciparum predominantly, remainder was P. vivax .species. Artesunate plus sulfadoxine-pyrimethamine were the first line treatment. Chloroquine showed resistance. Chemoprophylaxis and mosquito avoidance were recommended. Conclusion: Malaria control has reduced the incidence of disease over the last 15 years, there are only few cases in rural areas of Jeddah, Al Jouf and Jizan emirates by border of Yemen, reported in 2016. Saudi Arabia is on the way to eradicate malaria.
Keywords: Malaria; Plasmodium falciparum; KSA